Development of Articulate Storyline 360-Based Interactive Learning Media Integrated with PhET to Support the Implementation of the Merdeka Curriculum on Elements, Compounds, and Mixtures - Farisa Aina; Anisa Wulandari (Jurnal Pelita: Jurnal Pembelajaran IPA Terpadu, 2026)
The urgency of this research is to develop interactive learning media that integrates Articulate Storyline 360 and PhET simulations to enhance students' conceptual understanding of elements, compounds, and mixtures while supporting the effective implementation of the Merdeka Curriculum. Science learning in the Merdeka Curriculum requires the use of innovative media that actively involve students, but what happens in the field, the science learning process in schools often still relies on lecture methods and textbooks only, so that students feel bored and less enthusiastic during learning. This study aims to develop interactive learning media based on Articulate Storyline 360 ??on the material of elements, compounds, and mixtures for grade VIII SMP/MTs students in accordance with the Merdeka Curriculum. The method used is Research and Development (R&D) with the ADDIE development model, namely analysis, design, development, implementation, evaluation. The trial subjects consisted of 32 grade 8F students at MTsN 1 Nganjuk. The study was conducted over a period of two months, namely from April to May 2025. The instruments used were interviews and questionnaires. The results showed that the developed media obtained a feasibility percentage of 87% from material experts, 87% from media experts and 90% from student trials, this value is in the highly feasible criteria. The implementation results showed a positive response from students with a percentage of 86%, indicating that the product was attractive in terms of appearance, material presentation, and ease of access. Thus, interactive learning media based on Articulate Storyline 360 ??was declared suitable for use in science learning because it increased student enthusiasm and engagement in the learning process.